The Effects of Pore Pressure on the Mechanical and Physical Properties of Shales Effets de la pression de pore sur les propriétés physiques et mécaniques des argilites - Cook J. (Oil & Gas Science and Technology, 2006)
The title of this paper immediately raises two questions: what is meant by a shale, and what is meant by pore pressure in a shale? I will provide incomplete but workable answers to each of these, and discuss how the structure of shales influences their mechanical and physical properties. Le titre de cet article pose immédiatement deux questions : qu'entend-on par argilites, et qu'entend-on par pression de pore dans les argilites ? Je fournirai des réponses incomplètes mais utilisables, et j'examinerai comment la structure des argilites influence leurs propriétés mécaniques et physiques.